Efektivitas Iklan Produk Chocolicious Melalui Media Sosial Instagram - Tsalis Kurniawan Husain; Farizah Dhaifina Amran (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2021)
Chocolicious Indonesia is a company engaged in the downstream agribusiness industry that is actively conducting marketing activities through Instagram.  This research to analyzes the effectiveness of Chocolicious Indonesia’s products advertising through Instagram.  The method used is the descriptive analysis method. Sampling using the incidental sampling method with 100 respondents. The respondents are the followers of Chocolicious Indonesia’s Instagram account. This study conducted a validity and reliability test using SPSS software version 20. The analytical method used to measure the effectiveness of advertising is the EPIC model which includes four critical dimensions : empathy, persuasion, impact, and communication (EPIC).  The results showed that Chocolicious Indonesia’s product advertising through Instagram is very effective with a value of 4,21. The four dimensions measurement shows that the dimensions of empathy, persuasion, and communication are very effective. While the impact dimensions are in the effective category.